Who Represents the Poor? The Corrective Potential of Populism in Spain. Issue 4 (2nd October 2019) - Scantamburlo, Matthias
ABSTRACT: Scholarly research assumes populism enhances democratic inclusion by giving voice to groups that are not represented by political elites and by obliging them to be more attentive to their preferences. Empirical studies have focused on this dynamic more indirectly looking at the emergence of new conflict dimensions, leaving the representation of marginalised groups underexplored. This article contributes to filling this gap by analysing party competition over poverty responsiveness at the regional level in Spain during the Great Recession. Combining Regional Manifestos Project data with issue sub-categorisation, the article shows that populist parties, which emerged during the economic crisis, represent the poor to a greater degree in their political agenda than establishment parties. At the same time, the latter have reacted to new competitors by being more attentive to the poor in their political discourse. As a result, supply-side adaption to include proposals tackling poverty and social exclusion increased the representation of the poor in regional spaces of political competition.